A Review of Emotional Intelligence and Multicultural Competence in Indonesian University Students: Learning Style and Social Support as Major Predictors of Academic Achievement - Hendra , Robi; Denmar, Denny; Wijaya, Hansein Arif; Tomi, Masvil; Yusuf, Muhammad; Sembiring, Dian Arisandy Eka Putra; Putri, Dea Amelia Dwi (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2025)
This study examines how emotional intelligence (EI), multicultural competency (MC), learning style (LS), and social support (SS) affect university students' academic performance. In Jambi, Indonesia, 242 undergraduate students from three universities completed a five-point Likert-scale questionnaire. PLS-SEM with SmartPLS 3.0 tested the proposed relationships. Research indicates that learning style (β = 1.725, p < 0.001) and social support (β = 0.952, p < 0.001) significantly impact academic achievement, explaining 76.4% of its variance (R² = 0.764). Despite expectations, emotional intelligence (β = 0.072, p = 0.137) and multicultural competence (β = -0.030, p = 0.466) did not directly impact academic accomplishment. While multicultural competency negatively impacts learning style (β = -0.987, p < 0.001), social support is the biggest predictor of both learning style and academic accomplishment. Learning style and social support drive academic performance in the examined environment, while emotional intelligence and multicultural competency have minimal direct roles. The report recommends that colleges prioritize programs that help students identify and improve their learning styles and strengthen institutional and peer support systems above emotional intelligence and multicultural training. This study enhances our understanding of non-cognitive factors of academic success in multicultural Indonesian higher education. Keywords: PS-SEM, university students, Indonesia, academic performance, emotional intelligence, multicultural competency, learning style, social support